Asuhan Keperawatan Jiwa Pada Pasien Dengan Halusinasi Pendengaran Di Wisma Flamboyan RSJ. Prof. Dr. HB. Sa’anin Padang 2026 - Muhammad raif Raif; Dwi Happy Anggia Sari; Ramaita Ramaita; Vivi Yuderna (Jurnal Ilmu Psikologi dan Kesehatan | E-ISSN : 3063-1467, 2026)
Hallucinations are a type of mental disorder where a person cannot distinguish between real life and fake life. Based on data collection obtained from Prof. Hb Saanin Mental Hospital, Padang, the most common nursing diagnosis in 2026 was Hallucinations with a total of 6,062 patients. Researchers are interested in taking because is one of the patients who shows the most signs and symptoms of hallucinations. This researcher aims to apply Mental Nursing Care to with hallucinations at Wisma Flamboyan, Prof. Hb Saanin Mental Hospital, Padang. The implementation of Nursing Care to was carried out on February 5-11, 2026 with a visit of five days of meetings. The method of this Scientific Paper is in the form of a Case Study. The results of providing Mental Nursing Care were obtained by was able to control hallucinations independently by using implementation strategies (SP) and group activity therapy (TAK), namely SP 1 rebuke practice, SP 2 taking medication regularly, SP 3 having conversations, SP 4 carrying out scheduled daily activities. In this study, it is expected that understands the provision of Mental Health Nursing Care, as well as researchers, Prof. Hb Saanin Padang Mental Hospital and institutions are expected to be able to increase insight as a reference in providing optimal Mental Health Nursing Care.